The Prevent Alcohol and Risk-Related Trauma in Youth (P.A.R.T.Y) program: An interactive injury prevention initiative in South-Western Sydney. Issue 9 (September 2022) - Francis, Nevenka; He, Steven; Harris, Ian A.; Curtis, Kate; D'Amours, Scott K.; Frost, Steven A.
Highlights: To the authors' knowledge this is the first paper published evaluating the effectiveness of the P.A.R.T.Y program in Sydney, Australia. There were significant changes in participant perceptions towards risk-taking behaviours and their consequences, immediately post-program. Low response rates and decay in improvements 3-to-6-month post-program highlight need for continued engagement. Abstract: Background: The Prevent Alcohol and Risk Related Trauma in Youth (P.A.R.T.Y) program is an interactive injury prevention intervention, specifically designed for "at risk" youths aged 15 to 19 years. Emerging evidence has highlighted its positive impact on altering student attitudes towards risk-taking behaviour across several Australian and international settings. This study aims to describe the risk-taking behaviours of youths in South-Western and Greater Western Sydney, and assess the effectiveness of the Liverpool P.A.R.T.Y program to alter attitudes towards risk-taking. Methods: From 2015 to 2020, schools and youth organisations across South-Western and Greater Western Sydney were invited to participate in the Liverpool Hospital P.A.R.T.Y program. Youths aged 15 to 19 years were selected to attend by their respective teachers based on eligibility criteria. Knowledge and attitudes towards risk-taking behaviours were measured using surveys across three time points (pre-program, immediately post-program, 3-to-6 months post-program). Results: A total of 2544 participants from 50 schools and youth organisations attended the Liverpool Hospital P.A.R.T.Y program. There were 130 participants who did not record a response to a single question across all three time points and were omitted from analysis. Of the remaining 2414 participants, 49% were male, and 41% had access to a provisional driver's license or learner's permit. There were significant changes in knowledge and attitudes to risk-taking behaviours from pre-to immediately-post-program. A separate analysis across all three time points was conducted in response to a poor 3-to-6-month follow-up rate (25%). There was decay in improvements across all six questions, with the largest change seen in perceived likelihood of injury when engaging in physically risk-taking activities (52.2% to 36.9%, OR 0.44, 95% CI 0.33 – 0.60, p  < 0.001). Conclusion: This study demonstrated significant changes in participant attitudes towards risk-taking behaviours and their consequences, immediately after participating in the Liverpool Hospital P.A.R.T.Y program. However, the poor response rates at later follow-up highlight the need for ongoing engagement of the South-Western and Greater Western Sydney youths, to ensure these improvements are sustained.